The Role of Psychological Empowerment, Job Characteristic, and Reward System on Innovative Behavior - Nabila, Dinda; Mansyur, Anwar (Golden Ratio of Human Resource Management, 2026)
The research investigates how psychological empowerment, job characteristics, and reward systems influence innovative work behavior. Employees demonstrating innovative spirit are very important for an organization facing the ever-changing market dynamics. Data for this research were gathered quantitatively by distributing questionnaires to PT Aji Putra Jaya staff members. Purposive sampling is the method of sampling that is used. Multiple linear regression will be used to analyse the data after validity and reliability tests using SPSS. The research results are expected to show that psychological empowerment, job characteristics, and partial and simultaneous incentive schemes significantly and favourably influence creative work practices. The study aims to develop employee empowerment programs, redesign jobs to increase autonomy, and create a more relevant reward system to encourage innovation.